HUBUNGAN PENGETAHUAN MENGENAI MAKANAN CEPAT SAJI (FAST FOOD) DENGAN PERILAKU KONSUMSI MAKANAN CEPAT SAJI (FAST FOOD) PADA SISWA SEKOLAH MENENGAH ATAS PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - TRIYANTI, VIVI; Syarif, Winerlis; Chair, Ira Meirina (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The purpose of this study was to analyze the relationship between knowledge about fast food with fast food consumption behavior in high school students/SMA Pembangunan Laboratorium UNP . This research is a descriptive correlational nature . The population in this research was 685 people are students of class X , XI , and XII in SMA Pembangunan Laboratorium UNP . Based on the survey results revealed that students' knowledge about fast food achievement levels obtained by 59 % of respondents with a lower category . Student behavior in consuming fast food achievement levels obtained by 81 % of respondents with a high category . The magnitude of the correlation coefficient variable ( X ) and variable ( Y ) is 0.615 with the interpretation that the two variables are strongly correlated . The results showed that there is a positive and significant relationship between knowledge of fast food with fast food consumption behavior in SMA Pembangunan Laboratorium UNP. Keywords: knowledge, consumption behavior, fast food.